The Perception On Ulum Al-quran Course: A Comparative Study Between Research Universities - Mohammed Akhiruddin Ibrahim; Shahirah Sulaiman; Adnan Mohamed Yusoff; Zulkifli Haji Mohd Yusoff; Mohammad Hikmat Shaker (OCERINT International Organization Center of Acade, 2024)
Indexed by WOS